The Law as our Disciplinarian : A Critical Study of Galatians 3:24 in the Dagme Translations of the Bible - Kuwornu-Adjaottor, Jonathan E. T. (Ghana bulletin of theology, 2012)
Galatians 3:24 has to do with the function of the law before Christ came. The understanding of the word paidagogos and the phrase eis Christion are crucial to the translation, exegesis and interpretation of the verse. The way the verse has been rendered in the Dangme translations of theBible does not bring out the full meaning of the law as our paidagogos - "disciplinarian," "guardian," "custodian," "trainer" - before Christ came. This may promote antinomianism among Dangme Bible readers. It is being argued that the verse should be retranslated in the Dangme to bring out its full meaning.